Liquid Metal Gallium Micromachines Speed Up in Confining Channels. (21st November 2019) - Wang, Daolin; Lin, Zhihua; Zhou, Chang; Gao, Changyong; He, Qiang
Abstract : Liquid Metal Micromachines In article number 1900064, Changyong Gao, Qiang He, and co‐workers study the effect of confinement on the motion behavior of the liquid metal gallium machine. In the confining channels, the liquid metal gallium machine shows an adaptive deformation and speed‐up motion upon applying a direct current electric field.